Systematic versus Targeted Magnetic Resonance Imaging/Ultrasound Fusion Prostate Biopsy among Men with Visible Lesions. Issue 1 (24th January 2022) - Patel, Hiten D.; Koehne, Elizabeth L.; Shea, Steven M.; Fang, Andrew M.; Gorbonos, Alex; Quek, Marcus L.; Flanigan, Robert C.; Goldberg, Ari; Rais-Bahrami, Soroush; Gupta, Gopal N.
Abstract : Purpose: Multiparametric magnetic resonance imaging (mpMRI)-ultrasound (US) fusion-guided biopsy may improve prostate cancer (PCa) detection and reduce grade misclassification. We compared PCa detection rates on systematic, magnetic resonance imaging-targeted, and combined biopsy with evaluation of important subgroups. Materials and Methods: Men with clinical suspicion of harboring PCa from 2 institutions with visible Prostate Imaging–Reporting and Data System (PI-RADS TM v2) lesions receiving mpMRI-US fusion-guided prostate biopsy were included (2015–2020). Detection of PCa was categorized by grade group (GG). Clinically-significant PCa (csPCa) was defined as ≥GG2. Patients were stratified by biopsy setting and PI-RADS. Results: Of 1, 236 patients (647 biopsy-naïve) included, 626 (50.6%) harbored PCa and 412 (33.3%) had csPCa on combined biopsy. Detection of csPCa was 27.9% vs 23.3% (+4.6%) and GG1 PCa was 11.3% vs 17.8% (−6.5%) for targeted vs systematic cores. Benefit in csPCa detection was higher in the prior negative than biopsy-naïve setting (+7.8% [p <0.0001] vs +1.7% [p=0.3]) while reduction in GG1 PCa detection remained similar (−5.6% [p=0.0002] vs −7.3% [p=0.0001]). Targeted biopsy showed increased csPCa detection for PI-RADS 5, decrease in GG1 for PI-RADS 3, and both for PI-RADS 4 relative to systematic biopsy. Combined biopsy detected more csPCa (+10.0%) and slightly fewer GG1 PCa (−0.5%) compared to systematic alone. Upgrading to ≥GG2 by targeted biopsy occurred in 9.8% with no cancer and 23.6% with GG1 on systematic biopsy. Conclusions: Combined biopsy doubled the benefit of targeted biopsy alone in detection of csPCa without increasing GG1 PCa diagnoses relative to systematic biopsy. Utility of targeted biopsy was higher in the prior negative biopsy cohort, but advantages of combined biopsy were maintained regardless of biopsy history.